Hacia la convergencia del proceso penal en Europa y América - Reifarth Muñoz, Walter (Universidad de Colima, 2026)
Criminal Proceedings are the instrument by which the corrective force of the state is applied and which, undoubtedly, has the greatest level of acceptance within a democratic society and in which the exercise of authority to punish is subject to unwavering limits. Thus, this book intends to remember and reflect on some of the efforts which wake the ideals of liberty, democracy, institutional stability, equality, and the exaltation of human dignity.